FAKTOR RISIKO ERGONOMI DAN KESEHATAN KERJA PETANI PENGOLAH LAHAN PERTANIAN PADI BASAH - Widodo, Lamto; Djaha, Rymartin Jonsmith; Hidayat, Michael (Universitas Tarumanagara, 2025)
The agricultural sector is the backbone of the national economy, which is still dominated by manual work practices with high ergonomic risks. This impacts health, workplace accidents, and occupational diseases. This study aims to identify, analyze, and evaluate ergonomic risk factors in work activities in the agricultural sector, particularly in the process of preparing rice fields. This process consists of manual hoeing, manual land leveling, and land cultivation with a tractor. The study location is in Kolelet Village, Picung District, Pandeglang Regency, which is one of the rice granaries in Banten Province. The results of the Nordic Body Map (NBM) questionnaire showed that the most complaints were found in manual land leveling workers, followed by manual hoeing workers, and the least in tractor operators. The body parts most frequently experiencing musculoskeletal disorders (MSDs) were the shoulders, back, waist, arms, thighs, and calves. The results of the Rapid Upper Limb Assessment (REBA) analysis show that the work posture value for manual hoeing is 10 (High Risk), for manual land leveling the REBA value is 12 (Very High Risk), while for tractor operator work, the REBA value is 5 (Medium Risk). From the OWAS analysis, all three jobs are in the Red category, with the main factors being the workload and duration. For work environment conditions, 12:00 to 14:00 is the most dangerous hour with temperature, humidity in the danger category, and the UV index categorized as very high. The noise factor from the tractor sound ranges from 81-89 dB, still in safe conditions, with a work duration of between 2-6 hours a day.